Animasi 2D Sebagai Informasi Pelayanan E-KTP Kepada Masyarakat di Kantor Kecamatan Medan Denai: Array - Iskandar, Dicky; Harahap, herlina; Khairani, Sumi (Jurnal Ilmu Komputer dan Sistem Komputer Terapan (JIKSTRA), 2021)
This animation design is an information about the process of making KTP in Medan Denai District Office. Many residents do not know the process of making a KTP. For this reason, a method of delivering a KTP information is needed. The solution is to make 2D animation using adobe animation CC 2018. The process of making animation itself requires a story idea, scenario, story dialogue and storyboard. This animation provides information about an information process for making a KTP and explains the requirements for making a KTP. And there is a new policy from the government regarding the child identity card process. With this 2D animation, it is easier for the public to know the process of making a KTP so that there are no misunderstandings for officers, so that officers can provide the best service for the community